Effect of topical apraclonidine on flow properties of central retinal and ophthalmic arteries - Celiker, UO; Celebi, S; Celiker, H; Celebi, H (Scriptor Publisher, 1996)
To investigate the acute effects of topically administered 1% apraclonidine hydrochloride on blood velocity and resistance parameters of central retinal and ophthalmic arteries, the vessels were studied by color Doppler ultrasonography during baseline and at the time of peak effect of apraclonidine in 20 healthy volunteers, After medication, significant decrease in peak systolic, peak diastolic mean flow velocities and increase in resistive and pulsatility indices of ophthalmic artery were observed, Blood velocity and resistance parameters of central retinal artery didn't change significantly, In conclusion, topically used apraclonidine was thought to change the blood velocity and resistance parameters of ophthalmic artery as a result of its local vasoconstrictory effect on the anterior segment branches of ophthalmic artery.
Keywords: apraclonidine; color Doppler ultrasonography; central retinal artery; ophthalmic artery